Activating values to stimulate organic food purchases: can advertisements increase pro-environmental intentions?. Issue 5 (14th August 2017) - Bullock, Graham; Johnson, Christopher; Southwell, Brian
Abstract : Purpose: The purpose of this paper is to examine different strategies for an increasing adoption of "environmentally friendly" products. Scholars have consistently shown that consumers with strong biospheric and altruistic beliefs are more likely to purchase these products, while marketers are increasingly appealing to consumers' self-interest in their efforts to sell their "green" products. This paper explores this divide and offers a potential explanation for it, using the concept of value activation. Design/methodology/approach: The paper presents results of two survey experiments that test this explanation in the context of organic food advertisements. In a simulated trip to a grocery store, participants were exposed to advertisements designed to activate the six different values in Schwartz's framework. After viewing the advertisements, participants were asked to select among organic and non-organic options in six product categories – milk, bread, eggs, spinach, potatoes and chocolate. Findings: The study's results suggest that while advertisements designed to activate values may have limited effect on consumer intentions, those that relate to protecting the health of oneself and one's family are most likely to increase organic purchases. Originality/value: This paper is one of the first of its kind to explicitly test whether advertisements designed to activate a range of human values can increase consumers' intention to engage in pro-environmental behaviors. The two studies reveal that value-based advertisements may have a stronger effect on the organic purchasing intentions of specific demographic groups (e.g. consumers who are aged under 40, lack a college degree and do not identify as liberal).